Membangun kepemimpinan berkualitas melalui latihan dasar bagi siswa MTsN 4 Blitar - Prayoga, Rizki Dwi (Maliki Interdisciplinary Journal, 2024)
Leadership basic training is an essential aspect in shaping students' leadership character in school. This study explores the implementation of basic leadership training by the Student Council (OSIS) of MTsN 4 Blitar with the theme "Planning Together, Working with Enthusiasm". The philosophy behind this theme reflects values of collaboration, understanding, and enthusiasm in achieving common goals. Through a series of activities such as group discussions, role-playing simulations, and collaborative projects, students are guided to develop leadership skills, teamwork spirit, and ethical values. The results show improvements in students' leadership skills, self-confidence, communication abilities, collaboration, and conflict management. In conclusion, leadership training serves as an effective instrument in nurturing students' leadership potential before they become actual leaders in society.